Exploring longitudinal care histories for looked after children: a sequence analysis of administrative social care data - McGrath-Lone, Louise; Harron, Katie; Dearden, Lorraine; Gilbert, Ruth (International Journal of Population Data Science, 2018)
Background Outcomes for children in care vary by the stability of their placements (for example, more placement changes have been associated with poorer educational attainment). Official statistics describing the stability of care histories for children in England are limited to placement changes within a 12-month period. These annual statistical ‘snapshots’ cannot capture the complexity of children’s experiences; however, as administrative data have been routinely collected since 1992, it is possible to reconstruct longitudinal care histories. Objective To identify distinct patterns of care history by applying sequence analysis methods to longitudinal, administrative data. Methods We extracted care histories from birth to age 18 for a large, representative sample of children born 1992-94 (N=16,000) from routinely-collected Children Looked After Return data. We explored the heterogeneity of children’s care histories in terms of stability and identified sub-groups based on the number, duration and timing of placements using sequence analysis methods. Results Children’s care histories were varied with the number of placements ranging from 1 to 184 (median: 2). However, six distinct sub-groups of care history were evident including; adolescent entries (17.6%), long-term instability (13.1%) and early intervention (6.9%). Overall, most children (58.4%) had a care history that could be classified as’short-term care’ with an average of 276 days in care and 2.48 placements throughout childhood. Few children (4.0%) had a care history that could be described as ‘long-term stable care’. Conclusions Sequence analyses of longitudinal data can refine our understanding of how out-of-home care is used as a social care intervention. Despite the policy focus on achieving long-term stability for children in care, the vast majority of children remain in care for a short period of time. Future work exploring how outcomes vary between the different sub-groups of care history could enable better evaluation of the effects of longitudinal care experiences.